Corrective exercise solutions to common hip and shoulders dysfunction - Osar, Evan, ....- (Chichester : Lotus, 2014)
Dysfunctions of the movement system are at the core of most cases of musculoskeletal injury, including (but not limited to) degenerative joint conditions, impingement syndromes, and chronic myofascial and joint pain. These movement impairments result in repetitive and cumulative microtraumas that affect individuals in their occupations and everyday activities, as well as in their attempts to be more physically active during exercise or recreational activities. Full of color photographs illustrating precise assessments, corrective strategies, and functional progressions, Common Exercise Solutions to Common Hip and Shoulder Dysfunction demonstrates how the fitness professional/clinician can apply the three principles of human movement - respiration, centration, and integration - to improve common movement dysfunctions of the hip and shoulder. This valuable resource presents: The three reasons why clients develop faulty movement patterns - so the fitness professional/clinician can understand and explain the mechanisms behind their clients' hip and shoulder dysfunctions. The concepts and strategies, including the real-world and clinical application, of the corrective exercise and integrative movement approach to common movement dysfunctions of the hip and shoulder - so the fitness professional/clinician has both the strategies and the tools to address their clients' hip and shoulder dysfunctions. An easy-to-implement, principle-based solution to common movement dysfunction of the hip and shoulder - so the fitness professional/clinician can expand their expertise as a movement specialist and become a part of the solution to the health care crisis.
Includes on-line access to videos - schouderletsels - schouderaandoeningen - heupletsels - heupaandoeningen